Delay estimation via sliding mode for nonlinear time-delay systems. (March 2018) - Zheng, Gang; Polyakov, Andrey; Levant, Arie
Abstract: This paper deals with delay identifiability and delay estimation for a class of nonlinear time-delay systems. The theory of non-commutative rings is used to analyze the identifiability. In order to estimate the delay, a sliding mode technique and a classical Newton method are combined to show the possibility to have a local (or global) delay estimation for periodic (or aperiodic) delay signals.